ENVIRONMENTAL NOISE AND CARDIOVASCULAR DISEASES IN BULGARIA - Dima Tsanova; Tvetelina Vitkova; Atanas Anov; Emilia Bankova (Peytchinski Publishing, 2024)
Purpose: Noise has emerged as a leading environmental nuisance. Cardiovascular diseases rank first among the causes of death on a global scale and one of the possible effects of noise impact on the human organism. The study aims to analyze the level of noise pollution in Bulgaria and to measure its association with cardiovascular diseases. Methods: Data provided by the National Statistical Institute, Eurostat and other databases were used to analyze the noise pollution in Bulgaria. The 28 regions in Bulgaria were compared according to the proportion of surveyed points above permissible limits and the death rates due to cardiovascular diseases, /2022/. Data were statistically processed with SPSS v.26. Results: A positive fact is the absence of high values of noise levels in the range of 78-82 dB(A) and over 82 dB(A) and the decrease in the share of surveyed points with noise levels in this range during the analyzed period- from 27.3% in 2006 to 18.56% in 2022. The study found that almost all districts with the highest share of surveyed points above permissible limits have higher levels of death rate due to CVD. There is a positive moderate correlation between the share of surveyed points above permissible limits and the Death rate due to CVD - coefficient of Pearson is 0.423 (p=0.025). Conclusion: Cardiovascular diseases have a multifactorial genesis, but the reduction of noise in urban areas would help prevent these diseases.